Process Dryer Rubber Content of Crumb Rubber Products is The Ideal For Exploitation on Dryer Temperature and Timer of Range - Bursamin Bursamin (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to analyze the drying factor (DF) of crumb rubber products based on dry rubber content (DRC), time, and dryer temperature. Methodology: The study employed a completely randomized design (CRD) with two factors: temperature (80°C, 90°C, 100°C, 110°C, 120°C) and time (2, 4, 6 hours), each with 3 replications, and a control (100°C for 2 hours). Results: The results showed a significant interaction between time and dryer temperature. Temperatures of 90°C (4-6 hours), 110°C (2-4 hours), and 120°C (2-6 hours) can replace the standard 100°C for 4 hours without significant differences in DF. Finding: A temperature range of 110°C to 120°C for 4 hours prevents deviations in DRC standards. Novelty: This study identifies flexible temperature and time ranges for DF standards in crumb rubber products. Originality: It updates crumb rubber processing standards for quality optimization. Conclusions: Precise DF determination with appropriate temperature and time is crucial for crumb rubber product quality. Type of Paper: Quantitative experimental research.